Implementing participatory nature-based solutions in the Global South - Wolff, Erich; Rauf, Hanna A.; Diep, Loan; Natakun, Boonanan; Kelly, Kris; Hamel, Perrine (Frontiers in Sustainable Cities, 2022)
This article delves into the participatory aspects of the implementation of nature-based solutions (NbS) in the Global South. It examines the practices of community engagement in several projects conducted in informal settlements and how they relate to project visions. Building on previous work on community engagement for urban upgrading projects, we examine the relationship between the methods used to engage communities and the goals that guide the design and implementation of NbS. In doing so, we explore engagement practices that can support the emergence of transformative approaches in historically disadvantaged areas. We discuss how the degree of participation offered by different methods, such as citizen science and serious games, can substantially influence the outcomes of NbS projects by making them more integrated and site-specific. We conclude by discussing how the transformative implementation of NbS entails a multi-stakeholder proactive approach that is capable of supporting changes in the socio-ecological systems.